Community detection for directional neural networks inferred from EEG data - Ying Liu; Moser, J.; Aviyente, S. (2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2011)
One major challenge in neuroscience is to identify the functional modules from multichannel, multiple subjects recordings. Most research on community detection has focused on finding the association matrix based on functional connectivity, instead of effective connectivity, thus not capturing the causality in the network. In this paper, we propose a community detection algorithm suitable for weighted and asymmetric (directed) networks representing effective connectivity, and apply the algorithm to multichannel electroencephalogram (EEG) data. In addition, we extend the algorithm to find one common community structure from multiple subjects.